Caracterización del almidón de colocasia esculenta l. schott proveniente de los departamentos de Cajamarca y San Martín - Arguedas Deza, Frank Yudel (2008)
The characteristics physicist - chemistry of Colocasia esculenta (L). Schott "bituca" starch original of Cajamarca departments (Bambamarca district- Property in the country Orange tree) and St Martin (District New Cajamarca- Hamlet the Union) were analyzed. The following values were obtained in Selva/Sierra's samples: 43,2/36,59 % of starch in dry sample; the granule presented different forms: poliédrica, ovoid, romboydal, trapezoydal, with an average diameter that ranges of 0,8 - 7,77/0,93 - 3,16μm respectively measured to 4000x/5000x with the software Leica IM 1000, which has a micrometric scale adapted; the content of amylose was of 19,8/16,7 %; the degree of swelling was of 8/12,15 % to 70 º C and of 25,7/25 % to 90 º C; the solubility was a 13,3/13,3 to 70 º C and 26,6/27 to 90 º C; the sinéresis in the 21st to temperature environment was of 70/60 %. In conclusion the characteristics physicist - chemistry of the starch of both samples are similar except the size of the granule